A novel concept for self-healing metallic structural materials: Internal soldering of damage using low melting eutectics - L. Tanure; L. Patterer; S. Balakumar; M. Fekete; S. Mráz; S. Karimi Aghda; M. Hans; J.M. Schneider; H. Springer (Materials & Design)
A novel self-healing concept for metallic structural materials based on internal soldering using low-melting constituents is presented. The proof-of-principle study is based on a binary Al–4.28 wt%-Sn alloy, where a Sn-rich eutectic with a liquidus temperature of 228 °C acts as a self-assembling healing agent, and validated by a two-pronged approach: (i) A bulk sample with artificial damage is exploited to evaluate the healing effect on large cracks open to the sample surface and to gauge its mechanical effectiveness, whereas (ii) a 3.5 µm-thick Al2O3-Al-Sn-Al thin film multilayer architecture was used as a model system to study the healing mechanisms of small-scale internal damage induced by bending of the brittle Al2O3 layer. A crack length of ∼1.6 mm could be successfully re-filled by the low-melting eutectic with a simple annealing treatment at 400 °C for 30 min, which increased the bulk tensile ductility to more than 120 % compared to a similarly damaged pure Al sample. Furthermore, it is shown that the dispersion of the Sn-rich eutectic can be effectively controlled by utilising the polymorphy of Sn during material production. Alloy design perspectives for translating these findings towards industrial materials and applications are outlined and discussed.